Speaking Anxiety Experienced by The Fifth Semester Students of English Literature Department: A Case Study in Public Speaking Lesson - Mysi Lia Lisa Putri; Alfian Alfian; Putri Ayu Lestari (English Literature Department, Adab and Humanities Faculty, 2023)
This study is aimed to investigate the factors that contribute in speaking anxiety that experienced by the fifth semester students and the type of speaking anxiety in order to get the broader understanding about this phenomenon. This research is categorized as descriptive qualitative research. It involved the fifth semester students of English Literature Department 2022-2023 academic year as the participants. The data was collected through the interview. The findings of the research describe four factors that contribute in speaking anxiety and three types of anxiety. There were four factors based on Horwitz and Cope (1986) theory, the first factor is fear of negative evaluation (unconfident and overthinking) which made the student avoid do public speaking in English. Students were afraid because their mentality. The second is test anxiety (fear of performance in front of audience) which made the student avoid and afraid do the public speaking English. The third is communication apprehension (low speaking skill) which commonly happened on lack of vocabulary and unable to arrange the sentence and also stag in their mind. The fourth is new material which commonly happened on lack of understanding of new material. There were three types based on Horwitz (1986) theory, the first type of anxiety was trait anxiety it happened related when students fell unconfident and overthinking. The second type of anxiety was state anxiety. It happened relate on external factor and when someone feels being threatened. The third type was situation-specific anxiety. Due to low speaking skill seems like the students were afraid of being evaluated.